Analysis of stability condition for LDPC codes and optimizing degree sequences over mixed channel - Kang-ning SUN; Lin-hua MA; Le RU; Wen-tong FAN; Xing HU; Shao-cheng HUANG (Tongxin xuebao)
Under the circumstance that white Gaussian noise and random erasures exist all at once,the stability condition for LDPC codes over mixed channel was proposed.And it was proved that a good degree sequence of LDPC codes was not optimized over mixed channel.It can also be proved by simulation.The random particle swarm optimization (RPSO) and simulated annealing (SA) algorithm were combined to find some capacity-approaching degree sequences over mixed channel with different erasure probabilities.The threshold of signal-to-noise ratio improves 1.615 9 dB than that of the classical degree sequences calculated by Gaussian approximation over mixed channel.These degree sequences are optimal for optical recording and frequency-hopping communication with narrow-band interference.